Triboelectric Energy-Harvesting Floor Tile - Panu Thainiramit; Subhawat Jayasvasti; Phonexai Yingyong; Songmoung Nandrakwang; Don Isarakorn (Materials, 2022)
The aim of this study was to investigate the real-world electrical parameters that strongly affected the performance of a triboelectric energy-harvesting floor tile design: triboelectric material thickness, cover plate displacement distance or gap width, and cover plate pressing frequency, so that real-world specifications of the harvesting floor tile can be accurately specified. The structure of the designed triboelectric energy harvester, with readily available polytetrafluoroethylene (PTFE) film and aluminum foil, was simple and hence easy to fabricate, and the material cost was low. A square wave was used to simulate the pressing frequency on the test bench's cover plate. The results showed that the voltage and current were proportional to the gap width, and the thinner the triboelectric layer thickness, the higher the output voltage and current. A test bench with a 0.2 mm thick PTFE triboelectric layer generated the highest energy output. In a later experiment, a triboelectric energy-harvesting floor tile (TEHFT) prototype was constructed with 0.1 and 0.2 mm thick PTFE layers. We found that at 2 Hz stepping frequency and 0.1 mm PTFE thickness, the optimal load and cumulative energy of the TEHFT were 0.8 MΩ and 3.81 mJ, respectively, while with 0.2 mm PTFE thickness, these two parameters were 1.1 MΩ and 7.69 mJ, respectively. The TEHFT with 0.2 mm thick PTFE layer was able to illuminate a series of 100 to 150 LEDs, sufficient power to drive small electronics and sensor nodes. This discovery provides important data on the structure, material, and contact surface area of a TEHFT that can be adjusted to suit specific requirements of a special function triboelectric energy harvester.
Keywords: Advanced Sensor and Energy Harvesting Materials; Tactile and Sensory Interactions; Innovative Energy Harvesting Technologies